Supplier selection prioritizing sustainable criteria for products: an AHP approach in Peruvian public procurement - Cordero Torres, Bernardo (2019)
This paper focuses on sustainable public procurements that seek to minimize negative environmental impacts and improve positive social impacts, which require significant changes within the market reality of a country. In the case of Peru, legislation establishes the requirement that sustainable criteria be integrated into public procurement suited to the needs for the procurement of goods and services. In this way, the problem that this study seeks to resolve relies on technical non-observance to verify compliance with current regulations in force within the supplier selection process that consider sustainability criteria. Therefore, the application of the Hierarchy Analytic Process (AHP) is suggested as a heuristic solution alternative. This selection model makes it possible to improve the administrative process by increasing objectivity and reducing cognitive bias. To demonstrate this, the Analytic Hierarchy Process will be verified in a case study concerning the selection of LED lighting suppliers for a public institution.